Detecting Positive and Purifying Selection at Synonymous Sites in Yeast and Worm - Zhou, Tong (Oxford University Press, 2010)
We present a new computational method to identify positive and purifying selection at synonymous sites in yeast and worm. We define synonymous substitutions that change codons from preferred to unpreferred or vice versa as nonconservative synonymous substitutions and all other substitutions as conservative. Using a maximum-likelihood framework, we then test whether conservative and nonconservative synonymous substitutions occur at equal rates. Our approach replaces the standard rate of synonymous substitutions per synonymous site, dS, with two new rates, the conservative synonymous substitution rate (dS(C)) and the nonconservative synonymous substitution rate (dS(N)). Based on the ratio dS(N)/dS(C), we find that 0.05% of all yeast genes and none of worm genes show evidence of positive selection at synonymous sites (dS(N)/dS(C) > 1). On the other hand, 9.44% of all yeast genes and 5.12% of all worm genes show evidence of significant purifying selection on synonymous sites (dS(N)/dS(C) < 1). We also find that dS(N) correlates strongly with gene expression level, whereas the correlation between expression level and dS(C) is very weak. Thus, dS(N) captures most of the signal of selection for translational accuracy and speed, whereas dS(C) is not strongly influenced by this selection pressure. We suggest that the ratio dN/dS(C) may be more appropriate than the ratio dN/dS to identify positive or purifying selection on amino acids.